Nomenclatural notes and rediscovery of Viola cinerea var. stocksii (Violaceae) from Chambal ravines of Madhya Pradesh, India - Lohit, Tushar A.; Hurrah, Imtiyaz A.; Wagh, Vijay V. (Phytotaxa, 2022)
Viola cinerea var. stocksii is rediscovered from Chambal ravines of Madhya Pradesh after 52 years. It was also observed that the typification of Viola cinerea var. stocksii and its synonyms are inadequate. Original materials are also established here. In present communication detailed description, colour photographs and micrograph are provided for easy identification.